11.2% All‐Polymer Tandem Solar Cells with Simultaneously Improved Efficiency and Stability. Issue 36 (25th July 2018) - Zhang, Kai; Xia, Ruoxi; Fan, Baobing; Liu, Xiang; Wang, Zhenfeng; Dong, Sheng; Yip, Hin‐Lap; Ying, Lei; Huang, Fei; Cao, Yong
Abstract: All‐polymer solar cells (all‐PSCs) that contain both p‐type and n‐type polymeric materials blended together as light‐absorption layers have attracted much attention, since the blend of a polymeric donor and acceptor should present superior photochemical, thermal, and mechanical stability to those of small molecular‐based organic solar cells. In this work, the interfacial stability is studied by using highly stable all‐polymer solar cell as a platform. It is found that the thermally deposited metal electrode atoms can diffuse into the active layer during device storage, which consequently greatly decreases the power conversion efficiency. Fortunately, the diffusion of metal atoms can be slowed down and even blocked by using thicker interlayer materials, high‐glass‐transition‐temperature interlayer materials, or a tandem device structure. Learning from this, homojunction tandem all‐PSCs are successfully developed that simultaneously exhibit a record power conversion efficiency over 11% and remarkable stability with efficiency retaining 93% of the initial value after thermally aging at 80 °C for 1000 h. Abstract : Interfacial stability is studied by using a highly stable all‐polymer solar cell as a platform. The thermally deposited metal electrode atoms can diffuse into the active layer, which consequently greatly decreases the power conversion efficiency. Fortunately, the diffusion can be slowed down and even blocked by using thicker interlayer materials, high‐glass‐transition‐temperature interlayer materials and a tandem device structure.